Capn4 is induced by and required for Epstein‐Barr virus latent membrane protein 1 promotion of nasopharyngeal carcinoma metastasis through ERK/AP‐1 signaling. Issue 1 (25th November 2019) - Zheng, Peichan; Chen, Xiong; Xie, Jianqin; Chen, Xi; Lin, Shanshan; Ye, Lixiang; Chen, Lingfan; Lin, Jing; Yu, Xiangbin; Zheng, Ming
Abstract: Capn4, also known as CapnS1, is a member of the calpain family, which plays a crucial role in maintaining the activity and function of calpain. We previously reported that Capn4 also plays an essential role in the migration of nasopharyngeal carcinoma (NPC) cells through regulation of (MMP‐2) by nuclear factor‐kappa B activation. Epstein‐Barr virus latent membrane protein 1 (LMP1) is closely related to the malignant functions of NPC; however, the relationship between LMP1 and Capn4 in NPC remain unclear. Immunohistochemical studies showed that the level of LMP1 and Capn4 expression was high in both primary and metastatic NPC tissues, with a significantly positive correlation. We further found that LMP1 was able to upregulate the Capn4 promoter in a dose‐dependent way through the C‐terminal activation region (CTAR)1 and CTAR2 domains to activate AP‐1. Moreover, we also found that LMP1 activated AP‐1 through ERK/JNK phosphorylation. These findings indicate that Capn4 coordination with LMP1 promotes actin rearrangement and, ultimately, cellular migration. These results show that Capn4 coordination with LMP1 enhances NPC migration by increasing actin rearrangement involving ERK/JNK/AP‐1 signaling. Therapeutically, additional and more specific LMP1 and Capn4 targeted inhibitors could be exploited to treat NPC. Abstract : Capn4, also known as CapnS1, is a member of the calpain family, which plays a crucial role in maintaining the activity and function of calpain. In the present study, we found that Capn4 coordination with LMP1 enhances NPC migration by increasing actin rearrangement involving ERK/JNK/AP‐1 signaling.